Non-Fermi-liquid behavior: Exact results for ensembles of magnetic impurities - Zvyagin, A. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
In this work we consider several exactly solvable models of magnetic impurities in critical quantum antiferromagnetic spin chains and multichannel Kondo impurities. Their ground state properties are studied and the finite set of nonlinear integral equations, which exactly describe the thermodynamics of the models, is constructed. We obtain several analytic low-energy expressions for the temperature, magnetic field, and frequency dependences of importantcharacteristics of exactly solvable disordered quantum spin models and disordered multichannel Kondo impurities with essential many-body interactions. We show that the onlylow-energy parameter that gets renormalized is the velocity of the low-lying excitations (or the effective crossover scale connected with each impurity); the others appear to be universal. In our study several kinds of strong disorder important for experiments were used. Some ofthem produce low divergences in certain characteristics of our strongly disordered critical systems (compared with finite values for the homogeneous case or a single impurity). For weak disorder, or for narrow distributions of the local Kondo temperatures, our exact results revealthe presence of Kondo screening of disordered ensembles of magnetic impurities by low-lying excitations of the host. We point out that our results qualitatively coincide with the data ofexperiments on real disordered quasi-one-dimensional antiferromagnetic systems and with the similar behavior of some heavy metallic alloys.